Insights into Pleistocene palaeoenvironments and biostratigraphy in southern Buenos Aires province (Argentina) from continental deposits. - Beilinson, Elisa (2015)
The coastal cliffs of the Buenos Aires province (Argentina) have been the subject of intense paleontological studies since the XIX century. Therefore, many of the type localities in which is based the late Cenozoic Pampean biostratigraphic/chronostratigraphic scheme are located in this area. In this context, the sedimentites that crop out near the mouth of the Chocorí Creek contain a set of palaeontological sites that, because of their richness and well-preserved fossil content, hold high national and international importance. The aims of the present contribution are: 1) to make a stratigraphic and sedimentological characterization of the study area; 2) to list the fauna outcropped at these palaeontological sites and establish a biostratigraphic framework; 3) to elaborate a palaeoenvironmental model for the area. The study interval was informally subdivided into a lower, middle and upper interval. Interpretation was based on the presence of a number of key features such as architectural elements; channel:overbank ratio and palaeosol occurrence. The first two intervals were interpreted as continental deposits of a fluvio-alluvial nature and are the focus of this paper. The upper interval was related to foreshore marine deposits and will be studied in a future contribution. The lower interval is characterized mainly by overbank architectural elements in which calcisols and argillic protosols were identified. Channel-fill deposits are isolated and surrounded by fine-grained overbank successions and sedimentary structures are suggestive of mixed-load transport. The contact between the lower and middle intervals is an irregular, highly erosive surface characterized by a significant vertical change in the facies. This surface defines the base of multistorey sandbodies which's internal arrangement alongside with the low participation of overbank deposits suggests deposition by a braided fluvial system. Palaeosols and vertebrate fossils were used as palaeoclimatic, palaeoenvironmental and biostratigraphical proxies. Calcisol profiles, displaying Stages II to V morphologies (Machette, 1985), can be interpreted as evidence of periods of geomorphological stability that occurred under semi-arid to sub-humid climatic conditions. The occurrence of argillic Protosols stacked amongst the Calcisols evidence periods of relatively less stability, higher sediment supply and aggradation rates in the system. The vertebrate fossil assemblage and the invertebrate trace fossils also indicate semi-open landscapes under a seasonal, semi-arid climate. The presence of Platygonus, Glyptodon and Tolypeutes fossil remains in the lower interval suggest an Ensenadan age (middle Pleistocene) while the presence of Arctotherium bonariense in the V1 layer indicates post-Ensenadan (late Pleistocene) times for the middle interval. It is concluded that during accumulation of the Chocorí succession, glacio-eustasy and/or climate controlled the balance between generation of accommodation space and sediment supply. Analysis of the architectural elements indicates a general reduction in accommodation space. The lower interval represents the unconfined reaches of a large distributive system, more specifically, a low hierarchy, secondary drainage system inset in a high accommodation alluvial environment. The erosive surface identified at the base of the middle interval can be interpreted as representative of a period of negative accommodation in the system, when general erosion took place. The gradual restoration of accommodation in the fluvial system was accompanied by a low sediment accumulation rate and the development of a braided fluvial system in the middle interval.